Pudarnya Penerapan Sistem Ekonomi Islam Seiring Berkembangnya Sistem Ekonomi Kapitalis Pada Masyarakat Muslim Di Indonesia - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The economic system is based on a united mechanism and decision-making institutions that implement these decisions on production, consumption and income distribution. Therefore, the economic system is something that is important for a country's economy. The economic system is formed due to various complex factors, for example ideology and belief systems, worldviews, geographical environment, politics, social culture, and others. Islamic Economics refers to the interests of the world and the hereafter while the Capitalist Economy only refers to worldly interests. In the midst of the global economy as it is now, the contributions of Muslim scholars to economic thought have almost been forgotten, which appear to be only the thoughts of western scholars who are actually still very new. Thomas Kuhn said: Each system has a paradigm, so the core paradigm of Islamic Economics is certainl derived from the Qur'an And As Sunnah.